(untitled) (Journal of Asian Development Studies, 2025)
This study explores teachers’ perceptions, challenges, and approaches for supporting English competencies in public secondary school learners with communication anxiety in secondary study rooms. Eight educators from various schools participated in qualitative research through semi structured interviews to express their ideas and techniques. The findings indicate that English competencies, such as reading and writing, are often modelled and homogeneous in task challenges, whereas listening and speaking are frequently overlooked due to the critical backwards learning environment of public schools, which persists in the 21st century, as public school learners’ communicative skills are being compromised. Some teachers support learners’ communicative skills at their own pace to alleviate learners’ communication anxiety, which is a significant problem among students stemming from a lack of a solid study foundation. Other issues, such as interest, confidence, lack of motivation, or lack of practice, also arise. Fear of embarrassment and time restrictions make educating in English learning situations challenging. Furthermore, the results indicate that implementing a free anxiety environment facilitates feedback and reflection. It helps students raise confidence in foreign language acquisition, an important strategy to alleviate communication anxiety. Results are used to discuss the various techniques, as well as the pedagogical implications that could potentially follow. Only a teacher who creates an environment with excellent motivation and practice, and less anxiety, can help learners, regardless of their background, improve their communicative skills effectively and succeed in achieving proficiency at an international level. Furthermore, the research demonstrates that the pedagogical environment requires teachers to gain more knowledge, and contemporary technological accessories to support communicative skills and reduce communication anxiety among students in public secondary schools.